Direct Evidence That Sunbirds’ Gut Microbiota Degrades Floral Nectar’s Toxic Alkaloids - Gunasekaran, Mohanraj; Trabelcy, Beny; Izhaki, Ido; Halpern, Malka (Frontiers in Microbiology, 2021)
Orange-tufted sunbirds (Cinnyris osea) feed on the nectar of the tobacco tree (Nicotiana glauca) which contains toxic pyridine alkaloids characterized by high concentrations of anabasine and much lower concentrations of nicotine. We aimed at determining whether the gut microbiota of sunbirds harbour bacterial species that enable the birds to cope with these toxic alkaloids. An in vivo experiment that included 12 birds showed that inducing dysbiosis in sunbirds' guts by the addition of sulfamethoxazole and trimethoprim significantly reduced the birds' ability to degrade anabasine (n=3) compared to control birds (n=3) with undisturbed microbiota. Sunbirds whose gut bacterial communities were altered by the antibacterial agents and who were also fed with added nicotine also showed a lower percentage of nicotine degradation (n=3) in their excreta compared to the sunbirds with undisturbed microbiota (n=3), though, this difference was not significant. In an in vitro experiment, we studied the ability of Lactococcus lactis, Enterobacter hormaechei, Chryseobacterium gleum, Kocuria palustris, and Methylorubrum populi, that were isolated from sunbirds' excreta, to degrade anabasine and nicotine. By using gas chromatography-mass spectrometry analysis, we successfully demonstrated, for the first time, the ability of these species to degrade the focal secondary metabolites. Our findings demonstrate the role of gut bacteria in detoxifying toxic secondary metabolites found in the N. glauca nectar. The degradation products may supply the birds with nitrogen which is scarce in nectar-rich diets. These findings support another role of bacteria in mediating the interactions between plants and their pollinators.